Radiative-electron-capture-to-continuum cusp in U88+ + N2 collisions and the high-energy endpoint of electron-nucleus bremsstrahlung - Hillenbrand, Pierre-Michel; Hagmann, S.; Atanasov, D.; Banaś, D.; Blumenhagen, K.-H.; Brandau, C.; Chen, W.; De Filippo, E.; Gumberidze, A.; Guo, D. L.; Jakubassa-Amundsen, D. H.; Kovtun, Oleksiy; et al. (Physical review. A, Atomic, molecular, and optical physics, 2014)
The radiative electron capture of a target electron into the projectile continuum has been studied for the collision system U88N2→U88[N+2]∗+e−+γ at 90 MeV/u. Using a magnetic electron spectrometer, the energy distribution of cusp electrons emitted under an angle of 0∘ with respect to the projectile beam and with a velocity close to the projectile velocity has been measured in coincidence with the emitted photons under various observation angles. The experimental results provide a stringent test for the corresponding process in inverse kinematics, namely, the theory of electron-nucleus bremsstrahlung at the high-energy endpoint. For comparison this process is calculated using fully relativistic Dirac wave functions and using semirelativistic Sommerfeld-Maue wave functions.